Development of erosion induced landslides nomograph / Muhammad Solahuddeen Mohd Sabri - Mohd Sabri, Muhammad Solahuddeen (2015)
Erosion induced landslide is one of the important factor that contribute landslides process and is the most serious geological hazard in many part in the world. Previous landslides tragedy caused billions of money in property damage and thousands of deaths and injuries each year. The negligence of erosion induced landslide as one of the factors governing landslides need to be considered thoroughly. From this problem, the objectives of this research are to establish the erosion induced landslide nomograph and landslide risk level based on nomograph in predicting erosion induced landslide. In this research ,the development of erosion induced landslide risk level nomograph which involve on six factors of Universal Soil Loss Equation (USLE) are performed by data collection and soil sampling from 25 slope which are at Shah Alam and Puncak Alam, Selangor, Ulu Kelang, Ampang Selangor, Cameron Highland, Pahang and Hulu Langat Selangor. The information from the selected slope with regard to soil erodibility, rainfall erosivity index,slope steepness , slope length, cover management and management practices are analyzed to risk level nomograph. All of the factor will be total up in percentage and contributing to the development of the erosion induced landslide risk level nomograph thus producing the landslide risk level. The outcome of this research will help the agencies such as Public Works Department Malaysia (Slope Branch), Lembaga Lebuh Raya and local authority with new method in predicting with greater accuracy future erosion induced landslide risk level nomograph can be made known easier for citizens.